A revision of Biting Midges of the Subgenera Forcipomyia (Metaforcipomyia) and F. (Saliohelea) from Costa Rica (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2012)
The biting midge genus Forcipomyia Meigen, with 1,125 extant species placed in 35 subgenera (Borkent, 2012), is not only diverse in numbers of species but is also rich in morphological variation in each life stage. However, a tremendous amount of research is needed on this group before we will fully understand the true diversification of this genus. Our study of the species of two subgenera in Costa Rica illustrates how much yet remains to be done. Previously, there were no F. (Metaforcipomyia) Saunders known from Costa Rica and only one of F. (Saliohelea) Wirth & Ratanaworabhan. The discovery of 15 species of F. (Metaforcipomyia) (one previously described from elsewhere) and two of F. (Saliohelea) appears characteristic of our continuing investigation of the diversity in this remarkable genus.